Role of proximal femur locking plate fixation in certain unstable trochanteric fractures - Nageswaran, Jambu; Loganathan, Senthil; Ram, Ganesan Ganesan; S., Sumesh; Chittaranjan, Samuel (International Journal of Research in Medical Sciences, 2017)
Background: Comminution of the lateral trochanteric wall, postero-medial communition, reverse oblique fractures, fractures involving communition of greater trochanter are unstable fractures which had poor results with the regular methods of fixation. Our aim in this study is to evaluate radiological and functional outcome at the end of one year following proximal femur locking plate fixation for certain group of unstable intertrochanteric fractures. Methods: 20 patients (14 male and 6 female patients) with per trochanteric fractures underwent proximal femur locking plate fixation in Sri Ramachandra Medical College hospital. Intertrochanteric fractures were classified according to Boyd and Griffin. Mean age of the patients was 55.2 years (26-82 years). The Schatzker & Lambert Criteria used to evaluate the functional outcome at the end of one year. Minimum follow up period was six months and maximum follow up was one year. Results: The functional outcome was assessed by Schatzker and Lambert criteria and was excellent in 8 patients; good in 6, Fair in 4 and Poor in 2.The average time to bear weight fully and walk was 6.5 weeks. Conclusions: Union was achieved in unstable, comminuted trochanteric fractures without significant complications and neck shaft angle was maintained in majority of the cases following proximal femur locking plate fixation.One of the major drawbacks of using proximal femur locking plate is that weight bearing is to be controlled and done only after radiological evidence of callus formation.